Routine pin tract care in external fixation is unnecessary: A randomised, prospective, blinded controlled study - Camathias, Carlo; Valderrabano, Victor; Oberli, Hermann (Injury, 2012)
Pin site infections are seen in up to 40% of external fixators (ExFix) and are therefore the most common complication with this device. There is no consensus in the literature as to the appropriate regimen for pin tract care and infection prevention. This study is the first intra-subject, randomised, prospective controlled trial comparing daily pin tract care to no pin tract care at all. Consecutive patients series (56 patients, 16 female, age 4–68y, mean 24y, in total 204 pins) recruited in the National Referral Hospital in Honiara in the Solomon Islands over a 2 year period. Exclusion criteria were application of ExFix for less than two weeks or a non-standard ExFix. Pin treatment was allocated into groups anatomically, proximal and distal. Randomisation was intra-subject and intra-group: 101 pins had daily pin site care and 103 had no treatment at all. Soft-tissue interface, stability of the pins, torsional stability as determined with a torque metre, osteolysis and pain. Assessment of pin sites blinded. Statistical analysis using the paired t test for parametric data and the Wilcoxon rank test for non-parametric data (Stat View). No significant difference between the two groups. Soft-tissue interface 36% vs. 35% (granulation/secretion), stability 20 vs 25 pins with loosening. No significant osteolysis (7 vs. 6 pins). Torque: mean 0.75Nm, max.: 3.05Nm vs. 0.60Nm, max.: 3.55Nm, no significant difference. No differences in demographics (age, localisation, sex, time of fixation). This study shows that routine pin tract care is unnecessary in external fixation treatment of injuries.